2018
DOI: 10.1590/1678-4162-10130
|View full text |Cite
|
Sign up to set email alerts
|

O capim-marandu baixo no início do diferimento melhora a morfologia do pasto e aumenta o desempenho dos ovinos no inverno

Abstract: RESUMO Objetivou-se avaliar os efeitos de quatro alturas (15, 25, 35 e 45cm) da Urochloa brizantha cv. Marandu (capim-marandu) no início do diferimento sobre a morfologia do pasto, a seletividade e o desempenho de ovinos no início, meio e fim do período de pastejo, no inverno. Foi utilizado o delineamento inteiramente ao acaso, com três repetições. Os pastos diferidos com 35 e 45cm apresentaram maiores massas de forragem do que aqueles diferidos com 15 e 25cm. O pasto diferido com 15cm apresentou maior porcent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…Regarding the grazing period, this factor influenced, the following characteristics: CP, pdDM, iNDF contents, DM, CP and NDF intake, as well as DM digestibility (Table 3). At the beginning of the grazing period, there were higher content of pdDM, CP and DM digestibility (DDM) in the simulated grazing samples (Table 2; P<0.10) which were due to the higher percentage of live leafe and lower percentage of dead stem in these samples during the beginning of the grazing period, as verified by Afonso et al (2018) in a simultaneous study carried out in the same experimental area. During the period of use deferred pastures, in the winter, climatic conditions (temperature, photoperiod and, mainly, water availability) are limiting to pasture growth (Table 1).…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…Regarding the grazing period, this factor influenced, the following characteristics: CP, pdDM, iNDF contents, DM, CP and NDF intake, as well as DM digestibility (Table 3). At the beginning of the grazing period, there were higher content of pdDM, CP and DM digestibility (DDM) in the simulated grazing samples (Table 2; P<0.10) which were due to the higher percentage of live leafe and lower percentage of dead stem in these samples during the beginning of the grazing period, as verified by Afonso et al (2018) in a simultaneous study carried out in the same experimental area. During the period of use deferred pastures, in the winter, climatic conditions (temperature, photoperiod and, mainly, water availability) are limiting to pasture growth (Table 1).…”
Section: Resultsmentioning
confidence: 52%
“…Thus, deferred pastures with lower heights had better morphological composition. In this sense, Afonso et al (2018), in a study conducted concurrently in the same experimental area, verified that 15 and 25 cm deferred pastures had a higher percentage of live leaves in the simulation grazing samples, compared to the 35 cm 45 cm deferred pastures. Corroborating this, Santos et al (2008) also reported a negative correlation between dead stem mass and pdDM content (-0.85), but the correlation was positive between live leaf blade mass and pdDM content (+0.94) in deferred signalgrass (Brachiaria decumbens cv.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations